The role of organizational excellence and environmental regulation and policy on the relationship between TQM and sustainable performance in Malaysian food and beverage companies - Akanmu, Muslim Diekola (2021)
There have been inconsistent findings in the literature concerning the relationships between quality management and sustainable performance. Hence, this research has prompted a further investigation of the effect of other variables that may better explain the nature of these links. The main purpose of this study is to investigate the mediating and moderating effects of organizational excellence and environmental regulation and policy (ERP), respectively, on the relationship between total quality management (TQM) and sustainable performance (SP). Human resources management (HRM), service design (SD), information and analysis (IA), continuous process improvement (CP), benchmarking (BM), management leadership (ML), and quality assurance (QA) as TQM elements considered in this study were mediated and moderated with their respective relationships with sustainable performance. Questionnaires were distributed to 303 Malaysian food and beverage companies. 98 questionnaires were returned and used in the analysis using the PLS-SEM. The results of this study revealed that effective BM, CPI, SD, QA, and IA as TQM elements have a positive and significant effect on sustainable performance on one hand and organizational excellence as a significant mediator of ML, CPI, SD, HRM, and IA to sustainable performance on another hand. In contrast, the results indicated an insignificant moderating effect of environmental regulation and policy on the relationships between TQM practices and sustainable performance. This study supported the premises of the contingency and the institutional theory by reaffirming the importance of excellence for any successful strategic implementation in enhancing sustainable performance through the implementation of quality practices. The developed framework of this study can be employed by policy and decision-makers. Managers in the industry should consider the importance of this model when implementing any practice in the future. For future research, it is recommended that a longitudinal study is carried out to evaluate the impact of TQM, organizational excellence, and ERP on SP.